Mistake - Arowosaiye, Yusuf Ibrahim; Masum, Ahmad; Ali Mohamed, Ashgar Ali; Ahmad, Muhamad Hassan (CLJ Malaysia Sdn Bhd, 2024)
A mistake, from the perspective of contract law, has a narrower meaning than its ordinary lexicon definition. For this reason, the discussion on the meaning and effect of a mistake on a contract has remained a difficult topic to understand.1 It is because the scope of the element of mistake that may result in negative consent to a contract is not clearly defined, especially under the common law. This often leaves the courts with the onerous task of identifying deserving situations to nullify a contract on the ground of mistake as to the existence of certain facts that form the basis of obligations under the contract, as opposed to situations when parties want to renegade from their obligations.